Proceedings of the 11th ACM Conference on Embedded Networked Sensor Systems 2013
DOI: 10.1145/2517351.2517365
|View full text |Cite
|
Sign up to set email alerts
|

Powering indoor sensing with airflows

Abstract: Whereas a lot of efforts have been put on energy conservation in wireless sensor networks, the limited lifetime of these systems still hampers their practical deployments. This situation is further exacerbated indoors, as conventional energy harvesting (e.g., solar) ceases to work. To enable longlived indoor sensing, we report in this paper a self-sustaining sensing system that draws energy from indoor environments, adapts its duty-cycle to the harvested energy, and pays back the environment by enhancing the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Besides the already-existing mechanical vibrations, aeroelastic instabilities caused by air flows are increasingly employed to harness wind energy. Since wind is ubiquitous in both outdoor and indoor environments, it is a practical and effective energy source to power the sensing nodes (Wang and Inman 2013, Xiang et al 2013, Tan and Panda 2011.…”
Section: Introductionmentioning
confidence: 99%
“…Besides the already-existing mechanical vibrations, aeroelastic instabilities caused by air flows are increasingly employed to harness wind energy. Since wind is ubiquitous in both outdoor and indoor environments, it is a practical and effective energy source to power the sensing nodes (Wang and Inman 2013, Xiang et al 2013, Tan and Panda 2011.…”
Section: Introductionmentioning
confidence: 99%
“…Battery-powered wireless communications [18,19] using energy-harvesting technologies have been widely discussed with the objective of achieving self-sustainability to maintain service life [20]. Due to the intermittency and inconsistency of renewable energy sources, the sensor nodes will dynamically adjust the duty cycle [21] for long-term operation. A recent work [22] showed that it is better for a sensor node to adapt the data packet sending period according to environmental conditions to follow an energy-neutral policy; even if the battery is known to have enough energy, the node should not ignorantly execute tasks.…”
Section: Related Workmentioning
confidence: 99%
“…Nevertheless, building a self-sustaining EH-WSN remains a challenging task, especially in indoor environments where the harvested energy can be several orders of magnitude less than the consumed energy. For example, a typical, optimized application can spend milliwatts in sensing and communication, while the typical harvesting range for an indoor harvester remains on the order of microwatts [2,3]. Therefore, work to reduce power consumption is still required to achieve energy autonomy.…”
Section: Introductionmentioning
confidence: 99%